(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
This work relates the romantic movement and the creation of the Brazilian national identity, thinking about how these relationships are synthesized and manifested in the life and work of the poet from Maranhão, Gonçalves Dias, especially in the most famous of his poems, Canção do exílio. Thus, we will think about the process of building our identity and consolidating the process of political independence.